Z gamma production and limits on anomalous ZZ gamma and Z gamma gamma couplings in pp collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (Elsevier B.V., 2007)
We present a study of eey and mu mu gamma events using 1109 (1009) pb-(1) of data in the electron (muon) channel, respectively. These data were collected with the DO detector at the Fermilab Tevatron pp collider at Is = 1.96 TeV. Having observed 453 (515) candidates in the eey (jtAy) final state, we measure the Z gamma production cross section for a photon with transverse energy ET > 7 GeV, separation between the photon and leptons Delta Rey > 0.7, and invariant mass of the di-lepton pair Mee > 30 GeV/(2)(c), to be 4.96 0.30(stat. + syst.) zE 0.30(lumi.) pb, in agreement with the Standard Model prediction of 4.74 0.22 pb. This is the most precise Zy cross section measurement at a hadron collider. We set limits on anomalous trilinear Zyy and ZZy gauge boson couplings of -0.085 < h(30)(y) < 0.084, -0.0053 < h(40)(y) < 0.0054 and -0.083 < h(30)(Z) < 0.082, 30 40 30 -0.0053 < h(40)(Z) < 0.0054 at the 95% C.L. for the form-factor scale A = 1.2 TeV. 40 Published by Elsevier B.V.